2020
DOI: 10.1080/23746149.2020.1747945
|View full text |Cite
|
Sign up to set email alerts
|

Semiconductor/dielectric interface in organic field-effect transistors: charge transport, interfacial effects, and perspectives with 2D molecular crystals

Abstract: Organic field-effect transistors (OFETs) have been the hotspot in information science for many years as the most fundamental building blocks for state-of-the-art organic electronics. During the field-effect modulation of the semiconducting channel, the gate dielectric always has a significant influence on the charge transport behaviours. Hence, understanding of the nature of charge carriers at the semiconductor/dielectric interface and realizing functional OFETs with superior performance have been the cornerst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 129 publications
1
9
0
Order By: Relevance
“…Device characteristics under dry nitrogen show threshold voltage of −1.32 ± 0.77 V and device on-off ratios on the order of 10 3 (1247 ± 1556 V). Charge mobilities were calculated to be 1.34 ± 0.92 cm 2 V −1 s −1 at a gate voltage of −5 V, which is on the same order as other reported organic and carbon-based back gated transistors that range from 0.37 to 30 cm 2 V −1 s −1 ( Pei et al, 2020 ; Shiomi et al, 2019 ; Snow et al, 2005 ).
Fig.
…”
Section: Resultssupporting
confidence: 81%
“…Device characteristics under dry nitrogen show threshold voltage of −1.32 ± 0.77 V and device on-off ratios on the order of 10 3 (1247 ± 1556 V). Charge mobilities were calculated to be 1.34 ± 0.92 cm 2 V −1 s −1 at a gate voltage of −5 V, which is on the same order as other reported organic and carbon-based back gated transistors that range from 0.37 to 30 cm 2 V −1 s −1 ( Pei et al, 2020 ; Shiomi et al, 2019 ; Snow et al, 2005 ).
Fig.
…”
Section: Resultssupporting
confidence: 81%
“…Whereas structural defects in the film are common sources of charge trapping, charge trapping sites are also typically found at the device interfaces, which are related to a large variety of effects (chemical impurities, local morphology and structure variations, energetic disorder, etc. ). Although clarifying the sources of traps is a complex matter, the device improvements observed and rationalized in this work by the different treatments provide a better understanding of prevailing charge trapping mechanisms. We have observed that the vapor annealing of the films employing a polar solvent in which the OSC is not very soluble has given rise to a reduction of the shallow charge traps.…”
Section: Resultsmentioning
confidence: 92%
“…where T 0 = 8.5 × 10 3 K. (Figure 3b). [39] We like to point out, that for the temperature range between 350 K to 20 K, a poor fit was found for ln( )…”
Section: Charge Transportmentioning
confidence: 93%